2013
DOI: 10.1093/ntr/ntt126
|View full text |Cite
|
Sign up to set email alerts
|

Retail Tobacco Exposure: Using Geographic Analysis to Identify Areas With Excessively High Retail Density

Abstract: There is great disparity in tobacco outlet density (TOD), with density highest in low-income areas and areas with greater proportions of minority residents, and this disparity may affect cancer incidence. We sought to better understand the nature of this disparity by assessing how these socio-demographic factors relate to TOD at the national level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 20 publications
0
11
0
1
Order By: Relevance
“…Retail outlets were more likely to be present in areas that were low income. This level of increased exposure is likely to contribute to the perception that tobacco products are socially acceptable, which increases the likelihood of tobacco uptake and increases the difficulty in both making and succeeding in a quit attempt [ 25 , 26 ]. These findings are consistent with studies across North America that have found a relationship between socio-economic status and availability of tobacco products [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Retail outlets were more likely to be present in areas that were low income. This level of increased exposure is likely to contribute to the perception that tobacco products are socially acceptable, which increases the likelihood of tobacco uptake and increases the difficulty in both making and succeeding in a quit attempt [ 25 , 26 ]. These findings are consistent with studies across North America that have found a relationship between socio-economic status and availability of tobacco products [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…[13][14][15][16][17][18] In the USA, tobacco retailers concentrate disproportionately in neighbourhoods with a higher proportion of Black and Latino or Hispanic residents as well as neighbourhoods with lower socioeconomic status and those with a greater concentration of same-sex couples. [19][20][21][22][23][24] The past decade of research confirmed that a pattern of greater tobacco availability in areas of socioeconomic disadvantage is not unique to the USA, but also evident in Australia, Canada, Germany, Scotland and elsewhere. [25][26][27][28] Not surprisingly, differential exposures to pointof-sale tobacco marketing follow similar patterns.…”
Section: Prioritising Health Equitymentioning
confidence: 89%
“…We selected and report on the most relevant and illuminating documents, particularly those in which PMAI Research on placement of tobacco products in the retail spaces has been an accelerating area of tobacco control research (Abdel Magid et al, 2020;Anesetti-Rothermel et al, 2020;Glasser and Roberts, 2021;Lawman et al, 2020;Marsh et al, 2020;Marsh et al, 2021;Morrison et al, 2021;Pike et al, 2019;Pollay, 2007;Rodriguez et al, 2014;Shareck et al, 2020;Trapl et al, 2020;Valiente et al, 2020). Between 1999 and 2013, a few studies on tobacco retail placement were published in the international literature (Dewhirst, 2004;Feighery et al, 2003;Halonen et al, 2014;Lavack and Toth, 2006;Pollay, 2007;Rodriguez et al, 2014), then from 2016 increasing to more than a dozen (Abdel Magid et al, 2020;Anesetti-Rothermel et al, 2020;Glasser and Roberts, 2021;Lawman et al, 2020;Marsh et al, 2020;Marsh et al, 2021;Morrison et al, 2021;Pike et al, 2019;Shareck et al, 2020;Trapl et al, 2020;Valiente et al, 2020). Most studies on tobacco retail sales have been conducted in high-income countries, although a few studies have been conducted in Southeast Asia, including in Thailand (Li et al, 2015;Noosorn, 2019, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Since 2018, researchers have increasingly examined the density and proximity of retail shops to neighborhoods and schools with populations vulnerable to smoking. Some of this increase has been due to the availability of geographical mapping applications that can be used to analyze where tobacco retailers are located within specific populations (Morrison et al, 2021;Rodriguez et al, 2014;Valiente et al, 2020). A review of research findings on tobacco retailer density and proximity found that high densities of tobacco retailers are associated with factors that undermine tobacco control measures, reinforce tobacco use as a norm, and reinforce tobacco availability for youth initiation (Glasser and Roberts, 2021).…”
Section: Methodsmentioning
confidence: 99%